The Impact of Intravenous Lidocaine on ICP in Neurological Illness: A Systematic Review - F. A. Zeiler; N. Sader; C. J. Kazina (Critical Care Research and Practice)
Background. The goal of our study was to perform a systematic review of the literature to determine the effect that intravenous (IV) lidocaine had on ICP in patients with neurological illness. Methods. All articles are from MEDLINE, BIOSIS, EMBASE, Global Health, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to March 2015). The strength of evidence was adjudicated using both the Oxford and GRADE methodology. Results. Ten original articles were considered for the final review. There were 189 patients studied. Seven studies focused on prophylactic pretreatment with IV lidocaine to determine if there would be an attenuation of ICP spikes during stimulation, with 4 displaying an attenuation of ICP. Three studies focused on a therapeutic administration of IV lidocaine in order to determine ICP reduction effects. All therapeutic studies displayed a reduction in ICP. Conclusions. We cannot make a strong definitive recommendation on the effectiveness of IV lidocaine on the attenuation of ICP spikes during stimulation. There currently exists both Oxford 2b and GRADE B literature to support and refute the attenuation of ICP spikes with IV lidocaine during stimulation. There currently exists Oxford 2b, GRADE B evidence to support ICP reduction with lidocaine when used as a therapeutic agent.